Developing an Understanding of `Compromised Consent¿: How reconsideration of consent as a legal concept may inform a feminist theoretical framework for the introduction of `Nordic Model¿ prostitution laws and did inform the motivations of lawmakers in Ireland - Bacik, Ivana Catherine (Trinity College Dublin. School of Law. Discipline of Law, 2022)
The focus of this thesis is upon the development of prostitution law in Ireland leading up to and including the introduction of the so-called `Nordic model¿ approach into Irish law through Part 4 of the Criminal Law (Sexual Offences) Act 2017, which criminalises the purchase of sex. The Irish law change is considered in the context of a highly polarised theoretical debate within feminism, between those who see prostitution as `exploitation¿ and those who regard it as `work¿. Seeing prostituted sex as a necessarily exploitative `gender regime¿ is a position usually associated with radical or socialist feminist theories. This approach offers a justification for targeting demand by making it an offence to buy sex, thereby criminalising the (almost invariably male) client, while decriminalising those (predominantly women) engaged in selling sex. By contrast, the `sex work¿ approach, often deriving from liberal or postmodern feminist theoretical perspectives, seeks to offer a theoretical justification for legalising the buying and selling of sex. While the `sex work¿ perspective is currently dominant within academic discourse, policy-makers internationally are increasingly leaning towards the `exploitation¿ approach, with laws criminalising sex purchase being adopted in a growing number of jurisdictions. Such laws have however been subject to criticism by those from the opposing perspective, who assert that they offend against women¿s agency and legal capacity to consent. In order to develop theoretical and ideological justifications for the introduction of a `Nordic model¿ approach to prostitution law, this thesis reviews the legislative process leading to the passage of Part 4 of the 2017 Act in Ireland, and considers the aims and objectives of those engaged in policy-making. An Interpretive Policy Analysis (IPA) method is used, framed by an explicitly socialist feminist perspective, with a view to establishing whether a legal concept of `compromised consent¿, which it is argued implicitly informed the motivation of those proposing and supporting the 2017 legal change, may be used to advance a feminist theoretical argument justifying the introduction of laws in Ireland criminalising the purchase of sex. Throughout, the thesis relies upon the tools of policymaking analysis; including documentary analysis of Oireachtas debates, parliamentary reports and academic commentaries, along with a number of `elite interviews¿ carried out with key actors in the law-making process. The political and social context for the 2017 change is evaluated, and a review provided of the #MeToo movement and other relevant contemporary feminist campaigns, including that seeking a statutory definition of consent, which succeeded with the passage of section 48 of the 2017 Act. It is argued that insights from these other campaigns, along with contemporary intersectional socialist feminist theorising and the analysis of parliamentary debates, all provide support for a feminist re-consideration of consent as a legal concept. Even prior to the introduction of the new statutory definition in section 48, consent in Ireland was already seen as capable of being legally compromised in certain contexts of structured gender inequality, such as under-age sexual intercourse, domestic violence or workplace sexual harassment. The legal understanding of consent in such exploitative contexts is antithetical to the conception of consent as `freely and voluntarily¿ given within a mutual sexual relationship. This understanding of consent, it is argued, should be applied within the context of prostituted sex and prostitution, which itself may be understood as constituting a `gender regime¿. It is argued that the legal change may therefore be justified from a feminist perspective through a reappraisal of `consent¿ as capable of being legally compromised in certain contexts. This understanding of `compromised consent¿, it is suggested, can provide a robust feminist criminological basis for the introduction of the Nordic model approach into Irish law. Thus, the key objective of this thesis is to examine critically whether a legal concept of `compromised consent¿ may be helpful in informing a feminist theoretical argument justifying the introduction of laws criminalising the purchase of sex, with a specific focus upon the `Nordic model¿ change in prostitution law enacted in Ireland through the 2017 Act.
APPROVED
Keywords: Prostitution; Consent; Nordic Model; Feminist Criminology